Aristololactam alkaloids from the roots of Dasymaschalon rostratum. Issue 7 (3rd April 2021) - Wang, Yue; Chen, Wen-Hao; Song, Xiao-Ping; Han, Chang-Ri
Abstract: A novel aristololactam alkaloid, dasymalactam A (1 ), together with nine known analogues (2–10 ), were isolated from the roots of Dasymaschalon rostratum . Their structures were elucidated by IR, NMR and MS spectrums and comparisons with data reported in the literature. All compounds demonstrated weak cytotoxicity against Hela, MCF-7, A-549, MGC-803, and COLO-205 human cancer cell lines. Abstract :